“Terra do frio”, coronéis de “sangue quente”?: política, poder e alianças em Morro do Chapéu (1919-1926) - Leite, Jedean Gomes (2009)
This study aims to analyze a period of intense dispute for the local political power in Morro do Chapéu, State of Bahia, between the “coroneis” Antônio de Souza Benta and Teotônio Marques Dourado Filho, during the period of Brazilian history known as “República Velha”. The main issues presented in this work were the changes oc- curred in the municipality between the 1910s and 1920s; the relationship estab- lished between Souza Benta and his friend, “coronel” Francisco Dias Coelho; the alliances instituted as a way of maintaining the local power, among other things. The chronological scope covers the period between 1919, when Dias Coelho died, and 1926, with the solution of the impasse.